(untitled) (IAHS Medical Journal, 2024)
Background: Non-Communicable Diseases (NCDs) are now the leading causes of morbidity and mortality worldwide. Bangladesh has also experienced a rapid epidemiological shift from communicable diseases to non-communicable diseases due to growing urbanization and lifestyle alteration over the last few decades and this transition is also prominent in rural community of the country. Among all modifiable factors, overweight or obesity is the key risk factor for NCDs. This study aimed to determine the burden of NCD and its link to the body weight status of the rural population of Bangladesh. Materials and methods: This cross-sectional study was conducted in a village of Gomostapur Upazila under Chapainawabganj district from February to April 2024 among 135 people. The data were collected with face-to-face interview and Body Mass Index was measured. The data were compiled and tabulated according to key variables and analyzed with IBM SPSS 29.0.2. Results: Majority 44.5% of the study people belonged to age group 21-40 years. Among them 47.4% were male and 52.6% were female. Maximum respondents were of low-middle socioeconomic condition. Among them around 3/4th of the population was suffering from NCDs. Most of the respondents 24.4% had bone and joint pain followed by Hypertension, Asthma, COPD, Diabetes and Heart Disease at 20.7%, 17.0%, 14.1% and 10.4% respectively. Hypertension, Diabetes, Cardiovascular Disease, Stroke and Cancers were more prevalent in the older age group. Hypertension, Diabetes, Stroke and Bone-Joint Pain were seen more in female participants whereas male respondents had more prevalence of Asthma, COPD. Most of the study population had BMI above 25 kg/m2 and the study showed maximum NCDs were prevalent considerably in overweight and obese groups. Conclusion: The study revealed that, NCDs are highly prevalent among obese older rural population of Bangladesh while management, prevention, awareness and research are low. The integrated programs must be designed and implemented through a primary health care approach and high risk-group targeted interventions should be procurable to combat the rising burden of NCDs. IAHS Medical Journal Vol 7(1), June 2024; 74-79